2001
DOI: 10.1055/s-2001-11178
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Colonic Adenomatous Polyps Accompanied by a Migrated Surgical Suture

Abstract: A 56-year-old man and a 70-year-old woman, with histories of left colectomy and appendectomy respectively, were admitted to our hospital. In both cases, colonoscopy showed a pedunculated colonic polyp in the ascending colon, and a silk suture became visible in the stalk during polypectomy. The histological diagnosis was adenoma. These two cases constitute the first report of colonic adenomatous polyps accompanied by suture migration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…In recent years, a number of natural and synthetic biomaterials have been developed to design scaffolds . Because of their excellent biocompatibility and biodegradability, natural biomaterials, such as collagen, silk fibroin (SF), and chitosan, have drawn much attention in the fields of tissue engineering and other biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a number of natural and synthetic biomaterials have been developed to design scaffolds . Because of their excellent biocompatibility and biodegradability, natural biomaterials, such as collagen, silk fibroin (SF), and chitosan, have drawn much attention in the fields of tissue engineering and other biomedical applications …”
Section: Introductionmentioning
confidence: 99%
“…However, in our case and the cases of Fondran et al [ 11 ], because no remnant staple was found at the polyps, secondary ulceration and foreign body reaction of suture materials at the staple line was probably the cause of the inflammatory polyp. Therefore, chronic intramural stimulation during defecation may be a second possible cause for the formation of the rectal inflammatory granulation polyp, as in cases of silk sutures and vegetable seeds in colonic polyps [ 12 13 ]. However, Fondran et al [ 11 ] reported that in 2 of 9 patients, a polyp formed without suture reinforcement.…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanism underlying the migration of K-wires is unclear, prolonged mechanical factors, including muscular activity and regional reabsorption of bone, may have forced the Kwire to migrate from the pelvic bone to the pelvic cavity and protrude into the sigmoid colon in our case. In addition, chronic intramural stimulation of the migrated K-wire may have caused the development of the colonic inflammatory granulation polyp, as in cases of silk sutures and vegetable seeds in colonic polyps (9,10). Several recommendations have been made to prevent this potential complication (2).…”
Section: Case Reportmentioning
confidence: 99%